ASCL1 promotes Scrt2 expression in the neural tube - Goes, Carolina Purcell; Botezelli, Vitória Samartin; De La Cruz, Shirley Mirna; Cruz, Mário Costa; Azambuja, Ana Paula; Simoes-Costa, Marcos; Yan, Chao Yun Irene (Frontiers in Cell and Developmental Biology, 2024)
ASCL1 is a transcription factor that directs neural progenitors towards lineage differentiation. Although many of the molecular mechanisms underlying its action have been described, several of its targets remain unidentified. We identified in the chick genome a putative enhancer (cE1) upstream of the transcription factor Scratch2 (Scrt2) locus with a predicted heterodimerization motif for ASCL1 and POU3F2. In this study, we investigated the role of ASCL1 and this enhancer in regulating the expression of the Scrt2 in the embryonic spinal cord. We confirmed that cE1 region interacted with the Scrt2 promoter. cE1 was sufficient to mediate ASCL1-driven expression in the neural tube through the heterodimerization sites. Moreover, Scrt2 expression was inhibited both when we removed cE1 from the genome and when we modulated its epigenetic signature. These findings strongly indicate that ASCL1 regulates Scrt2 transcription in the neural tube through cE1.